Medication Belief and Adherence among Patients with Epilepsy - Yirga Legesse Niriayo; Abraham Mamo; Kidu Gidey; Gebre Teklemariam Demoz (Behavioural Neurology, 2019)
Background. Medication adherence and belief are crucial to achieving the desired goal of therapy in epileptic patients. However, there is a lack of study regarding medication adherence and belief in our setting. Therefore, the purpose of this study was to investigate medication adherence and belief and associated factors among ambulatory patients with epilepsy. Method. A cross-sectional study was conducted on randomly selected epileptic patients at the neurologic clinic of Ayder Comprehensive Specialized Hospital, Ethiopia. Medication adherence and belief were assessed using self-reported questionnaires which were developed based on the review of different literatures. Data were analyzed using binary logistic regression analysis. Result. We included a total of 292 patients. Almost two-thirds (65.4%) of the patients were nonadherent to their medications. The most common cause of nonadherence was forgetfulness (48.7%) followed by inability to get medicine (28.8) and safety concern (23.5%). The majority (78.4%) of the patients had high medication necessity belief while 44.1% had high concern belief about the potential adverse effect of their medications. Overall, 39.4% of the patients had a negative belief toward their medications. Comorbidity (AOR: 3.51, 95% CI: 1.20-10.31), seizure encounter within the last 3 months (AOR: 5.45, 95% CI: 2.48-12.00), low medication necessity belief (AOR: 3.38, 95% CI: 1.14-10.00), high medication concern belief (AOR: 4.23, 95% CI: 2.07-8.63), and negative medication belief (AOR: 4.17, 95% CI: 1.74-10.02) were predictors of medication nonadherence. Conclusion. Majority of the epileptic patients were nonadherent to their medications, and more than one-third of the patients had a negative medication belief. Low medication necessity belief, high medication concern belief, negative medication belief, comorbidity, and seizure encounter were predictors of medication nonadherence. Therefore, healthcare providers should design educational programs to enhance the patients’ believe about their medication in order to improve medication adherence and overall treatment outcome.